2019
DOI: 10.1021/acs.nanolett.9b02696
|View full text |Cite
|
Sign up to set email alerts
|

A Reconfigurable Remotely Epitaxial VO2 Electrical Heterostructure

Abstract: The reconfigurability of the electrical heterostructure featured with external variables, such as temperature, voltage, and strain, enabled electronic/optical phase transition in functional layers has great potential for future photonics, computing, and adaptive circuits. VO2 has been regarded as an archetypal phase transition building block with superior metal–insulator transition characteristics. However, the reconfigurable VO2-based heterostructure and the associated devices are rare due to the fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…The remote epitaxy proposed by earlier studies [1][2][3][4][5][6][7][8] was validated mainly by the surface potential distribution calculated over a space layer complying with that of a substrate. We discussed some questions raised from the previous calculations in Supplementary Note3.…”
Section: Computational Evidence Questioning Remote Epitaxymentioning
confidence: 97%
See 1 more Smart Citation
“…The remote epitaxy proposed by earlier studies [1][2][3][4][5][6][7][8] was validated mainly by the surface potential distribution calculated over a space layer complying with that of a substrate. We discussed some questions raised from the previous calculations in Supplementary Note3.…”
Section: Computational Evidence Questioning Remote Epitaxymentioning
confidence: 97%
“…[1][2][3] Several other studies have also demonstrated the facile detachment of a film taken as evidence of remote epitaxy. [4][5][6][7][8] Strictly speaking, however, the easy detachability may not necessarily originate from the 'remoteness' of the remote epitaxy, but simply indicates that the binding between the film and space layer/substrate is weaker than the adhesion of the film to a detacher such as a thermal release tape. In fact, the entire remoteness of the remote epitaxy across the interface has never been rigorously verified yet.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, surfaces of the released and transferred TiO 2 NM are uniform and intact without any defective boundaries 31 . Figure 2d shows that the entire area of TiO 2 films with lateral dimension of millimeter-scale and nanometer thickness was fully released from the VO 2 /TiO 2 substrates after this etching process.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the monolayer graphene does not completely screen the electrostatic potential of the substrate, which enables the epilayer to follow the crystalline template of the substrate [ 10 , 11 ]. The remote epitaxy and graphene-mediated exfoliation have been demonstrated for several material systems, including III-N [ 8 , 9 , 11 , 12 ], III-V [ 10 ], II-VI [ 9 ], transition metal dichalcogenides [ 13 ], perovskites [ 14 ], and other complex oxides [ 15 ].…”
Section: Introductionmentioning
confidence: 99%